ANALISIS ECONOMIC VALUE ADDED (EVA) TERHADAP RETURN SAHAM PERUSAHAAN JAA BEI - Melmusi, Zerni (Jurnal Ekobistek, 2012)
This study aims to analyze the financial information regarding Economic Value Added (EVA) to return shares in property & real estate services in exchange with the time period of 2007 until 2011 as an alternative in the decision to invest in the capital market. The sample used by 15 companies from a total of 52 populations belonging to the classification of property services sector and real estate, after the analysis is based on measuring instruments used are 9 companies that tend to be positive EVA and 3 companies have a positive stock returns. Correlation testing was conducted by Karl Pearson Correlation and Kolmogorov Smirnov normality test, correlation EVA as dependent variables and Stock Return as independent variables with 95% confidence level. From the test results it is concluded that the correlate of Economic Value Added (EVA) and Stock Return happens to have a strong positive correlation. Key Words : Economic Value Added (EVA), Stock Return